FY 92-97 Bean/Cowpea CRSP; five-year Project Extension Proposal - National Bean Programme (National Bean Programme, 1990)
The project rationale, previous year's objectives, and major accomplishments of the Bean/Cowpea Collaborative Research Support Program are summarized. Five-year (1992-97) project extension goals are described as to research in biological sciences and research, training, and impact expected in social sciences. The anticipated contributions are enumerated and the workplan is described for research objectives (specific objectives and methods, project logistics, and expected outcomes), training program, project integration, and budget request. (CIAT)